CELEBRITY ENDORSEMENT AND BRAND IMAGE IN AESTHETIC SERVICE ADOPTION - Seftiana, Angelita; Fatimah, Feti; Rahayu, Jekti (Univesitas Muhammadiyah Tangerang, 2025)
A company to achieve its goals depends on how the company controls the market because market control depends on the company whether the company can anticipate every opportunity and threat that will come to the company such as changes in its marketing environment and anticipate every change that occurs in the environment and use the right information in making purchasing decisions. The decision to purchase a product will be more effective if assisted by several strategies, namelycelebrityendorsement, brand image, and social media marketing. This study aims to analyze the influence ofcelebrityendorsement, brand image, and social media marketingtoConsumer purchasing decisions at the Larissa Aesthetic Center Clinic Jember. This study uses a quantitative research method with a descriptive approach. The population in this study were consumers of the Larissa Aestethic Center Jember Beauty Clinic. The number of samples in this study was 100 respondents. This study used a non-probability sampling technique. The analysis technique used was multiple linear regression analysis. The results of this study indicate that partially the variablescelebrityEndorsement, brand image, and social media marketing have a positive and significant influence on consumer purchasing decisions at the Larissa Aesthetic Center Clinic, Jember.